Emerging Virus Infections in Adverse Pregnancy Outcomes - Baud, David; Pomar, Léo (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In this Special Issue of Viruses, we present original research, reviews and commentaries that contribute to improving our understanding of the viral infection of placenta and fetal cells, or that report on the maternal and fetal outcomes after an emerging viral infection during pregnancy.